GENETIC PREDISPOSITION TO PERIODONTAL DISEASES: MYTH OR REALITY? - Yusupjanova Nigora Davrbek qizi (Research Focus International Scientific Journal, 2025)
Periodontal diseases, including gingivitis and periodontitis, are among the most prevalent oral health conditions worldwide. While bacterial infections are considered the primary cause, increasing evidence suggests a genetic component in disease susceptibility. This article explores the role of genetic predisposition in periodontal diseases through a comprehensive analysis of family-based studies, twin studies, genome-wide association studies (GWAS), and epigenetic influences. The findings highlight that while genetics play a role, environmental and behavioral factors significantly modulate disease expression. The implications of genetic research for personalized periodontal treatment are also discussed.